Recognition of seasonal effect on captive Sumatran Sambar deer reproductive cyclicity and sexual behaviors - HERI DWI PUTRANTO; EDI SOETRISNO; NURMEILIASARI NURMEILIASARI; AHMAD ZUENI; BERRY GIBSON (Society for Indonesian Biodiversity, 2010)
Putranto HD, Soetrisno E, Nurmeiliasari, Zueni A, Gibson B (2010) Recognition of seasonal effect on captive Sumatran Sambar deer reproductive cyclicity and sexual behaviors. Biodiversitas 11: 200-203. The objective of this study was to identify seasonal effect on reproductive cyclicity of a captive female Sumatran sambar deer by monitoring its visual estrus manifestations and visual sexual behaviors in buck during female natural estrus in ex situ habitat. A pair of six years of age Sumatran sambar deer was used in this study.Daily observation of visual estrus manifestations of doe and visual sexual behaviors of buck was conducted using focal-animal sampling by two animal keepers during 0800 to 1700 h from June-July 2009 (dry season) to August-September 2009 (rainy season). Doe visual estrus manifestations include apparent reddening and swelling of the external genitalia, loss of appetite and a natural tendency of the doe to approach the buck. There was no significant effect of season on doe visual estrus manifestations and buck sexual behaviors (p > 0.05),except for loss of appetite and fighting behavior, respectively. Estrus was observed monthly and result of the cycle was 25.00 Â± 5.22 days. It is possible to assess non-invasively estrous cycle of Sumatran sambar deer by the observation of visual estrus manifestations and there was less of seasonal effect on doe-buck sexual behaviors during female natural estrus in ex situ habitat.Key words: estrous cycle, sambar deer, seasonal effect, sexual behavior.